Conservation of Cultural Heritage in Indonesia: A Review of Policy and Practice - Lubis, Lunariana; Wardiyanto, Bintoro; Setijaningrum, Erna (Universitas Sultan Ageng Tirtayasa, 2024)
: Since 2010, the Indonesian government has given ministries and local governments the power to designate cultural heritage. However, there are still few clear policies and planning for cultural heritage conservation, so this study aims to find gaps in existing policy and planning and propose a revised policy framework. The method used a qualitative based on literature review. The examination of Indonesia's policy framework for cultural heritage conservation revealed a number of flaws that have an impact on the process. A heritage-owner approach to conservation, a lack of financial sources, a lack of incentives, a lack of openness, and poor coverage of the context of heritage are some of these shortcomings. The political structure should be revised, integrated conservation strategies and incentives should be offered, financing sources should be diversified, and public participation should be increased in order to address these deficiencies.